Genetic Regulation of ERK1/2–c-Fos Signalling Pathway in Newcastle Disease Virus–Induced Apoptosis of Human Pancreatic Cancer Stem Cells - Ghasemi, Seyed Abbas; Sekawi, Zamberi; Ling, King-Hwa; Ismail, Saila; Chau, De-Ming (Malaysian Journal of Medical Sciences, 2026)
Background: Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive cancer with a five-year survival of approximately 6% that is largely driven by cancer stem cells (CSCs), which promote resistance, metastasis, and recurrence. Mutations in the Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (K-RAS) are common in human PDAC and activate the rat sarcoma (RAS) pathway, thus supporting tumour growth, maintenance, and metastasis. Newcastle Disease Virus (NDV) is a tumour-selective oncolytic virus with a strong safety profile that targets cancer cells and therapy-resistant CSCs, thereby highlighting its potential as an anticancer virotherapy. This study examines NDV AF2240’s ability to target CSCs through RAS pathway modulation and apoptosis induction.Methods: NDV AF2240 was titrated by hemagglutination (HA) and plaque assays using Vero cells. CSCs were isolated from Panc-1 cells and confirmed by sphere-formation, flow cytometry, and RT-qPCR for CD24, CD44, and EpCAM/ESA. Cells were infected at multiplicities of infection (MOIs) of 0.1, 0.5, 1, and 10 for 24–72 h. Cytopathic effects were assessed with an MTS assay, and apoptosis was assessed by the expression of Caspase-3, -8, and -9, Bax, and Bcl-2. NDV reduced CSC viability in a time- and dose-dependent manner, with significant declines at 24–48 and 72 h (P < 0.05). Apoptosis markers Caspase-3, -8, and -9, and Bcl-2 were significantly upregulated (M = 3.4613, 5.9173, 2.4610, and 2.2083, respectively; P < 0.05). An MOI of 0.1 was used for pathway analysis in 1 × 10⁶ CSCs.Results: NDV AF2240 induced effective cytopathic effects in PDAC stem cells, downregulating the K-RAS effectors ERK1/2 and C-FOS, triggering apoptosis, and reducing the viability of PDAC CSCs in vitro.Conclusion: These findings highlight NDV’s potential as an oncolytic agent against PDAC stem cells via the modulation of ERK1/2 and C-FOS, thus supporting its therapeutic development.